2002
DOI: 10.1007/bf02492320
|View full text |Cite
|
Sign up to set email alerts
|

Application of thin-layer chromatography with fluorescence scanning densitometry for analysing saturates in heavy liquids derived from Co-pyrolysis of biomass and plastics

Abstract: SummaryTwo alternative methods, based on Thin-Layer Chromatography (TLC) with Fluorescence Scanning Densitometry have been developed for characterization of heavy liquids from copyrolysis of different kinds of biomass and plastics in autoclaves under inert atmosphere.A conventional TLC system, which includes a vertical developing tank, and a High Performance TLC (HPTLC) system, with a horizontal developing chamberand the use of HPTLC plates, have been used. The analytical method involves in both cases the meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It was reported that, when a silica gel plate is impregnated with a solution of berberine cation, the application onto the layer of a paraffinic compound produces an increase in the fluorescence signal (between 450 and 550 nm) when the system is irradiated with UV light at 365 nm. , This fluorescence was exclusively due to the sample in the presence of berberine, and its intensity was in proportion to sample load and alkylic chain length. This phenomenon has been used to develop analytical procedures for detecting saturated hydrocarbons in diesel fuels and other fossil fuel-derived products. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that, when a silica gel plate is impregnated with a solution of berberine cation, the application onto the layer of a paraffinic compound produces an increase in the fluorescence signal (between 450 and 550 nm) when the system is irradiated with UV light at 365 nm. , This fluorescence was exclusively due to the sample in the presence of berberine, and its intensity was in proportion to sample load and alkylic chain length. This phenomenon has been used to develop analytical procedures for detecting saturated hydrocarbons in diesel fuels and other fossil fuel-derived products. , …”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon has been used to develop analytical procedures for detecting saturated hydrocarbons in diesel fuels and other fossil fuel-derived products. 14,[18][19][20][21] Many other molecules induce a change in berberine fluorescence baseline. Lipids also provide an enhanced emission signal, 4 whereas molecules with higher polarity induce decreases of fluorescence intensity, as shown in Figure 1 in the case of the studied amino acids, proteins, and rifampicine, an antibiotic.…”
Section: Resultsmentioning
confidence: 99%
“…In recent work, the mixtures of synthetic polymers such as polypropylene (PP) or polyethylene (PE) and wood biomass have been studied to develop new energy source as solid, oil and gas forms. Thus, the cofiring of both polymer and wood chip can give various advantages such as recycle of waste resource and improved utilization of wood chip as solid fuel [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It should be stated here that biomass is also composite polymeric material. Thermochemical conversions especially pyrolysis of biomass and polymer blends have been studied for a decade and it has steadily been increasing in recent years [33][34][35][36][37][38][39][40]. Environmental impacts of wastes exert pressure on governments and researchers to conduct experimental investigations especially on polymeric wastes.…”
Section: Introductionmentioning
confidence: 99%